Kajian Tri Tangtu di Buana Konservasi Air Situ Sipatahunan: Studi Kasus: Situ Sipatahunan, Kabupaten Bandung - Tresna Fuji Ilahi; Weishaguna (Bandung Conference Series: Urban & Regional Planning, 2022)
Abstract. This study focuses on the issue of the need to establish a water conservation zone based on the Sundanese landscape in the Situ Sipatahunan area. The urgency of this study is based on interests regarding the urgency of the environment, the urgency of heritage, and the urgency of the local community. This study focuses on the question of how to classify the tri tangtu water conservation zone in the Situ Sipatahunan area. Therefore, the purpose of this study is to identify the classification of water conservation zones in the Situ Sipatahunan area according to Tri tangtu di buana. The approach used to solve the problem is the tri tangtu di buana concept approach which includes buana nyungcung, buana panca tengah, and buana larang. Each zone was analyzed with four variables and criteria which include topography, land use, conservation elements according to the Sundanese landscape, and the presence of sites and culture. This study uses a qualitative hermeneutic method with a comparative analysis method that is focused on comparing the existing data with the tri tangtu criteria in the water conservation area and validated with other supporting theoretical foundations. Based on the results of the analysis, there were three land classifications in the delineation of the Situ Sipatahunan area, namely Buana nyungcung as an upstream zone which functioned as a water conservation or water catchment zone, Buana panca tengah as a middle zone functioned as a water cultivation zone, and Buana larang as a downstream zone functioned as a protection zone. local (buffer). Abstrak. Studi ini berfokus pada isu kebutuhan penetapan zona konservasi air berdasarkan tata buana sunda di Kawasan Situ Sipatahunan. Urgensi studi ini didasari kepentingan mengenai urgensi lingkungan, urgensi heritage, dan urgensi komunitas lokal setempat. Studi ini berfokus pada pertanyaan bagaimana klasifikasi tri tangtu zona konservasi air di Kawasan Situ Sipatahunan. Oleh karena itu, tujuan studi ini yakni mengidentifikasi klasifikasi zona konservasi air di kawasan Situ Sipatahunan menurut Tri tangtu di buana. Pendekatan yang digunakan untuk memecahkan masalah tersebut dengan pendekatan konsep tri tangtu di buana yang meliputi buana nyungcung, buana panca tengah, dan buana larang. Masing-masing zona dianalisis dengan empat variable dan kriteria yang meliputi topografi, tata guna lahan, elemen konservasi menurut tata buana sunda, dan keberadaan situs dan kebudayaan. Studi ini menggunakan metode kualitatif hermeneutic dengan metode analisis komparasi yang difokuskan dengan cara membandingkan data eksisting dengan kriteria tri tangtu di buana konservasi air dan dilakukan validasi dengan landasan teori pendukung lainnya. Berdasarkan hasil analisis didapatkan tiga klasifikasi lahan pada deliniasi Kawasan Situ Sipatahunan yaitu Buana nyungcung sebagai zona hulu yang difungsikan sebagai zona konservasi air atau resapan air, Buana panca tengah sebagai zona tengah difungsikan sebagai zona budidaya air, dan Buana larang sebagai zona hilir difungsikan sebagai zona perlindungan setempat (buffer).